2020
DOI: 10.31234/osf.io/qusxf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racial disparities in the sharing economy: Evidence from more than 100,000 Airbnb hosts across 14 countries

Abstract: Online peer-to-peer platforms aim to reduce anonymity and increase trust by displaying personal information about sellers. However, consumers may also rely on the names and profile photos of sellers to avoid sellers from certain social groups. Here we analyze more than 100,000 Airbnb rentals to test whether consumers discriminate against hosts from racial minorities. If consumers prefer to stay with a White host, then hosts from racial minorities should be able to charger lower prices for similar rentals. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, a study on Airbnb revealed that hosts who had never hosted African American guests were less likely to accept guests with African American names compared to those with White names (Edelman et al, 2017). Another analysis showed that non-White hosts charge 2.5-3% lower prices for similar listings, while Black and Asian hosts charge approximately 5-7% and 4-6% less respectively (Jaeger and Sleegers, 2020). It was also found that discrimination between hosts and guests on Airbnb is reciprocal, with specific topics in reviews and self-descriptions significantly associated with discrimination (Zhang et al, 2022).…”
Section: Consumer Fairness: Individual and Group Discriminationsmentioning
confidence: 97%
“…For example, a study on Airbnb revealed that hosts who had never hosted African American guests were less likely to accept guests with African American names compared to those with White names (Edelman et al, 2017). Another analysis showed that non-White hosts charge 2.5-3% lower prices for similar listings, while Black and Asian hosts charge approximately 5-7% and 4-6% less respectively (Jaeger and Sleegers, 2020). It was also found that discrimination between hosts and guests on Airbnb is reciprocal, with specific topics in reviews and self-descriptions significantly associated with discrimination (Zhang et al, 2022).…”
Section: Consumer Fairness: Individual and Group Discriminationsmentioning
confidence: 97%
“…Airbnb Non-White hosts charge lower prices for qualitatively similar rentals than white hosts (Jaeger and Sleegers, 2020) The presence of ethnic groups (Maghreb and South America) in the neighborhood negatively impacts Airbnb listing price in M alaga, Spain (Chica-Olmo et al, 2020) The listing price of Airbnb Hispanic and Asian hosts are on average lower relative to their White counterparts in San Francisco (Kakar et al, 2016(Kakar et al, , 2018 Asian hosts on average earn less per week compared to White hosts for similar Airbnb rentals (Wang et al, 2015)…”
Section: ) Minoritymentioning
confidence: 99%
“…For example, a study on Airbnb revealed that hosts who had never hosted African American guests were less likely to accept guests with African American names compared to those with White names (Edelman et al, 2017 ). Another analysis showed that non-White hosts charge 2.5–3% lower prices for similar listings, while Black and Asian hosts charge approximately 5–7% and 4–6% less respectively (Jaeger and Sleegers, 2020 ). It was also found that discrimination between hosts and guests on Airbnb is reciprocal, with specific topics in reviews and self-descriptions significantly associated with discrimination (Zhang et al, 2022 ).…”
Section: Individual Stakeholder Fairness In Trsmentioning
confidence: 99%